Development and quality evaluation of cookies enriched with various levels of grapefruit pomace powder - Kausar, Tusneem; Saeed, Esha; Hussain, Ashiq; Firdous, Nida; Bibi, Barira; Kabir, Khurram; Ul An, Qurat; Ali, Muhammad Qasim; Najam, Ayesha; Ahmed, Adnan; Yaqub, Shazia; Elkhedir, Abdeen Elsiddig (Springer Nature, 2024)
Grapefruit pomace, has been considered a valuable waste byproduct and a rich source of health promoting and functional components. The present work aims to prepare a flour by hot air drying of grapefruit pomace, in order to explore and incorporate it into the formulation of cookies at a level of 0, 5, 10 and 15% replacement with the straight grade wheat flour. The effect of grapefruit pomace powder on the physical, bioactive, chemical, textural and organoleptic properties of the cookies was assessed. Results showed the presence of 8.25% fibre, 9.63% ash, 8.96 mg/GAE g total phenolic content, 3.64 mg QE/g total flavonoid content, 2.05 mg/g total carotenoid contents and 42.12% antioxidant activity (DPPH assay) in the grapefruit pomace powder. The addition of pomace powder at varying amount in the cookies resulted in significant (p < 0.05) change in the chemical and bioactive composition. A significant increase in the fibre (1.58–3.10%), ash content (0.58–1.25%) and fat (20.19–22.05%) and significant decrease in crude protein content (6.79–5.20%) was observed in the cookies having 0–15% grapefruit pomace powder. Similarly, bioactive contents and antioxidant activity of the cookies was also significantly (p < 0.05) increased as the level of incorporation of grapefruit pomace powder was increased. Significant changes in the physical properties of the cookies were also observed, as diameter and thickness were decreased and hardness of the cookies was increased. Cookies containing 10% grapefruit pomace powder got significantly high scores in terms of taste and overall acceptability. It could be concluded that the use of grapefruit pomace powder has potential to enhance the nutritional and antioxidant potential of the cookies.